1974
DOI: 10.3382/ps.0530918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Lighting Regimes on Diurnal Rhythms of EEG Components in the Chicken

Abstract: Godet, J., D. Schiirch and V. Nigon, 1970b. Caracterisation et evolution des hemoglobines dans le cours du developpement postembryonnaire chez la poule. J. Embry. Exp. Morph. 23: 153-167. Konitzer, K., and K. Michalke, 1965. Der eisenstoffweschel der weissen Mous Ausscheichung und organ verterlung einen Fe 59 tracer dosis. Acta Biol. Med. Germ. 14: 489-495. Ramsay, W. N. M., 1966. The incorporation of iron into hemoglobin in the domestic fowl. Quat. J. Exp. Physiol. 51: 221-228. Rusov, C, 1965. Recherches sur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Circadian rhythmicity in the fowls has been reported for locomotor activity (Siegel, Beane & Kramer, 1962), feeding behaviour (Weaver & Siegel, 1968), intestinal motility (Oshima, Shimada & Tonone, 1974), e.e.g. patterns (Yano, Oshima & Gotoh, 1974), heart rate (Scott & van Tienhoven, 1971;Oshima, Shimada & Tonone, 1974), body and brain temperatures (Simpson & Gallbraith, 1904;Winget, Averkin & Fryer, 1965;Scott & van Tienhoven, 1971). There are however only few studies on rhythmicity in metabolic rate despite its implications, specifically in farm animals, on the nutritional and environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythmicity in the fowls has been reported for locomotor activity (Siegel, Beane & Kramer, 1962), feeding behaviour (Weaver & Siegel, 1968), intestinal motility (Oshima, Shimada & Tonone, 1974), e.e.g. patterns (Yano, Oshima & Gotoh, 1974), heart rate (Scott & van Tienhoven, 1971;Oshima, Shimada & Tonone, 1974), body and brain temperatures (Simpson & Gallbraith, 1904;Winget, Averkin & Fryer, 1965;Scott & van Tienhoven, 1971). There are however only few studies on rhythmicity in metabolic rate despite its implications, specifically in farm animals, on the nutritional and environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In the domestic bird, diurnal variation occurs in various physiological processes [1,5,10,15,19,22,[27][28][29]. When T lymphocytes were collected at various time intervals dur ing a 24-hour cycle, a variation was ob served in the migratory activity of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, deep body temperature showed a clear circadian rhythm even under constant illumination [28]. Yano et al [29] also alluded to a cir cadian rhythm of EEG components of hens under constant illumination. They also ob served changes in slow wave production im mediately prior to turning off the light which suggested the existence of some time measuring mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blokhuis (1983) observed that hens prepared for rest during the hour preceding dusk and became active again during the hour preceding dawn. Yano et al (1974) reported a photoperiodically controlled rhythmicity of activity, as indicated by EEG slow wave components. An immediate rise in slow wave rate was observed at dusk, followed by a gradual decrease during the dark period and an abrupt fall at dawn.…”
Section: Introductionmentioning
confidence: 98%